Halal Sport Tourism: Study on Potential, Accessibility, and Management Models in Lombok, West Nusa Tenggara - Endraswati, Hikmah; Solihan, Munif; Shofi'unnafi, Shofi'unnafi; Bonang, Dahlia; Kusuma, Bayu Mitra A. (Fakultas Dakwah dan Ilmu Komunikasi UIN Antasari Banjarmasin, 2025)
The objectives of this research are: (1) To explore the potential and opportunities for Halal Sport Tourism in Lombok to bring in tourists. (2) mapping the fulfillment of facilities and infrastructure in making it easier for tourists to reach locations and activities at Halal Sport Tourism locations in Lombok. (3) Analyzing the participation of tourism actors (stakeholders) in the management of Halal Sport Tourism in Lombok. The method in this study uses a type of qualitative research using a descriptive approach. The results of this study show that the potential for Halal Sport Tourism in Lombok is actually quite large, this is shown by the existence of Sport Tourism Events, Active Sport Tourism, and some nostalgia for Sport Tourism in various places in Lombok. this is also strengthened by the existence of supporting infrastructure such as quite a lot of places of worship, Lombok is also predominantly Muslim so that halal guarantees in every sports tourism area can be ascertained to be halal. In terms of accessibility, accommodation already exists and this is good, this is indicated by the existence of several sharia hotels, then the ease of direct transportation to Muslim countries and regions, as well as guarantees of halal restaurants in the sports tourism area and easy access to purification and worship for tourists. The management model is an illustration of how the concept of Halal Sport Tourism can be developed. Currently, this special tourism interest has not been developed there. However, seeing the existing potential and access, Halal Sport Tourism has the potential to be developed further. Management of existing halal tourism and sports tourism can be integrated as a model for managing Halal Sport Tourism in the future.